Glenoid fossa position in skeletal class-II malocclusion due to retrognathic mandible and skeletal class-I malocclusion in Pakistani population - Rabia Tabassum; Nazish Amjad; Faiza Malik (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Different dental and skeletal abnormalities interact with each other to cause multiple malocclusions of various areas of the dentofacial region. Association of the mandible and cranial base influence the malocclusions in anteroposterior and vertical dimensions that influences the evaluation of the skeletal components of a particular patient, so the relationship of glenoid fossa to adjacent craniofacial components must be taken into account. This research is conducted for the comparison of glenoid fossa position in subjects presenting with class II skeletal malocclusion due to retrognathic mandible and class I skeletal malocclusion.METHODOLOGY: Standardized lateral cephalograms of 130 patients were selected according to inclusion criteria from the orthodontic department. These radiographs were traced, and different angular and linear measurements were recorded. Then the position of glenoid fossa was compared in subjects of class II malocclusion with retrognathic mandible and class I malocclusion. SPSS version 17 was used for data analysis. Cephalometric measurements were analyzed, and glenoid fossa position was compared in both groups by using student’s t-test. Statistical level of significance using student t test was p< 0.05RESULTS: Position of glenoid fossa in subjects with class II malocclusion is more distal and posterior as compared to the subjects with class I malocclusion. The effective parameters for the measurements of glenoid fossa are GF-S on FH, GF-Ptm on FH, and GF-FMN with p value 0.0001.CONCLUSION: A distally and posteriorly placed glenoid fossa is an important diagnostic feature of Class II skeletal malocclusion with the retrognathic mandible.